INTEGRATION OF ISLAMIC PARENTING AND FAMILY COUNSELING: A STRATEGY TO CREATE A MODERN SAMARA FAMILY - Akbar, Sika Raemif; Sri Hidayati (International Journal of Multidisciplinary Reseach, 2025)
This study aims to conceptually examine Islamic parenting from the perspective of family counseling as a strategy for establishing a harmonious, loving, and blessed household. The study employed a literature review method with a descriptive qualitative approach, drawing on various scientific sources related to Islamic parenting and family counseling grounded in Islamic values. The results of the study indicate that Islamic parenting is based on the principles of compassion (rahmah), exemplary behavior (uswah), justice ('adl), and spiritual responsibility. Meanwhile, family counseling in Islam serves as a preventive and therapeutic tool for addressing family issues, fostering emotional connections, and instilling spiritual values within the household. The integration of Islamic parenting and family counseling yields a holistic family development strategy, adaptable to the challenges of the times, yet rooted in Islamic teachings. This study provides theoretical contributions to the development of Islamic education and family counseling as well as practical recommendations for parents, educators, and religious institutions in building families that are sakinah, mawaddah, wa rahmah.